Characterization of physical, chemical, and mineralogical properties of acid sulfate soils of the State - Combatt Caballero, Enrique Miguel; Lani, Joao L.; Alvarez V., Victor H. (Revista de Ciencias Agrícolas, 2014)
The influence of sulfate reduction conditions on the physical, chemical, and clay and sand mineralogical properties of six soil profiles was studied, in order to perform an analysis of the acid sulfate soils in the valley of Suruacá and Linhares in the state of Espirito Santo, Brazil, and in the Sinú river valley in Córdoba, Colombia. The work was aimed at characterizing acid sulfate soils in order to provide information on management practices that enable sustainability of agricultural production these soils. The definition and description of the study areas was carried out through photo interpretation and field work, followed by a laboratory analysis of the collected soil. The physical analysis of these soils characterized them as sandy clay loam and silty loam texture, due to a high distribution percentage of silt and sand in the soils. Chemically, the soils have saline characteristics, with presence of oxidation and reduction processes, as well as an extremely acidenvironment with highlevels of exchangeable aluminum, notwithstanding the high base content. The clay fraction mineralogy is composed of vermiculite, illite, and kaolinite minerals and the sand fraction is composed of sand quartz and muscovite mica.